Emerging Urinary Markers of Renal Injury in Obstructive Nephropathy. (2nd July 2014) - Lucarelli, Giuseppe; Mancini, Vito; Galleggiante, Vanessa; Rutigliano, Monica; Vavallo, Antonio; Battaglia, Michele; Ditonno, Pasquale
Abstract : The effects of obstruction on renal function are the consequence of many factors that profoundly alter all components of glomerular function. Besides the acute effects on glomerular filtration rate and tubule function, a chronic obstruction induces tubular and interstitial injury that results from the activation of different pathways. The progression of tubulointerstitial injury leads to chronic renal damage characterized by tubular atrophy, inflammatory cell infiltration, and interstitial fibrosis. Obstructive nephropathy is an evolving disease in which the renal damage continues even after relief of the obstruction. In particular, it has been demonstrated that the time of relief is the most important factor in predicting long-term renal function deterioration. In this setting, the EGF/MCP-1 ratio, urinary NGAL, and urinary KIM-1 are useful early biomarkers of progressive renal damage and could have a potential role in predicting the long-term renal outcome. This minireview summarizes the role of these emerging urinary biomarkers of obstructive nephropathy based on the current understanding of the pathophysiology of renal injury.